Nature of HIV/AIDS information shared on social media sites by undergraduate students in Southwestern Nigeria (2017)
In the past 5 years, there has been a phenomenal increase in the use of social media for health information communication, despite this, not much study has looked at the type of HIV/AIDS information shared on social media platform. The study therefore assessed the nature of HIV/AIDS information shared on social media sites by undergraduate students in southwestern Nigeria. Structured questionnaire copies were administered to 355 undergraduate students in Obafemi Awolowo University (OAU), University of Lagos (Unilag) and University of Ibadan (UI). Data gathered from the administered questionnaire were analyzed using descriptive and inferential statistics. Result showed that 71.3% of the students across the selected universities were aware of social media and made used of it. Facebook was the most favourite social media platform followed by Instagram and WhatsApp, while Kinschat, Linkedln, Skype and BBM were least preferred social media sites. Independent samples test result showed there was no significant gender difference in the preference of social media sites (t = 1.039, p>0.05). The result showed that 81.4% of the students had come across HIV/AIDS information on social media, while only 24.8% had shared HIV/AIDS information on social media. Prevention methods and general HIV/AIDS knowledge were the main types of information shared. ANOVA result further revealed significant variation in the type of HIV/AIDS information shared on social media among the three universities (F = 5.177; p<0.05). The Post Hoc Test of multiple comparison indicated that type of HIV/AIDS information shared in UI differed significantly from those shared in OAU and UNILAG respectively.